Description of two new fossil echinoids (Echinodermata: Echinoidea) from the Early Hauterivian (Early Cretaceous) of the Paris Basin (France) - Saucède, Thomas; Dudicourt, Jean-Christophe; Courville, Philippe (Zootaxa, 2012)
Two new echinoid genera and species, Salvaster roberti gen. et sp. nov. and Pygolampas edita gen. et sp. nov. are de-scribed. They were collected in the Calcaires à Spatangues Formation (CSF) that consists of limestone and clay sedimentsdeposited in the southeast of the Paris Basin (France) during the Early Hauterivian (Early Cretaceous). The CSF is datedfrom the Acanthodiscus radiatus chronozone, a time-interval of overall high sea level in Western Europe, but it yields arich shallow-water fossil fauna mostly represented by benthic invertebrates. Of the 54 echinoid species ever described inthe CSF, 26 species are recognized here. They are distributed into 16 different families, among which regular (13 species)and irregular (13 species) echinoids are represented in equal proportion. This work confirms the high level of echinoid diversity in the CSF for that time-period.